Amniotic fluid index, single deepest pocket and transvaginal cervical length: Parameter of predictive delivery latency in preterm premature rupture of membranes - Young-Joo Lee; Seung-Chul Kim; Jong-Kil Joo; Dong-Hyung Lee; Ki-Hyung Kim; Kyu-Sup Lee (Elsevier, 2018)
Objective: Prediction of delivery latency complicated with preterm premature rupture of membrane (PPROM) is crucial for reducing maternal and neonatal complications. Therefore, we investigated the correlations between latency period and cut-off values of ultrasonographic parameters, ultimately predicting delivery latency. Materials and methods: The retrospective study was performed on 121 PPROM patients enrolled between March 2010 and July 2015. Parameters including amniotic fluid index (AFI), single deepest pocket (SDP) and transvaginal cervical length (TVCL) were measured in 99 singleton pregnancies with PPROM. Latency was defined as the period from sonographic measurements to delivery day. The parameters were analyzed independently by Wilcoxon rank sum test and Fisher's exact test. Cut-off values were determined using a receiver operating characteristic (ROC) curve. Results: In delivery latency within 3 days, AFI and SDP were decreased with significantly shorter TVCL. AFI and SDP had the highest sensitivity (82.2%) and SDP combined with TVCL showed the highest specificity (75.9%) in area under curve (AUC) value. The predicted median latency period was less than 2 days within the cutoff value of parameter (AFI ≤ 7.72, SDP ≤ 3.2 and TVCL ≤ 1.69). Conclusion: AFI and SDP combined with TVCL could be useful predictive parameters of the latency interval from PPROM to delivery.